(untitled) (Third Sector Social Economic Review, 2018)
The European Union (EU) is one of the longest established political, legal, economic and socio-cultural means of integration. By the end of 2017, the Union had 28 members and included 10 of these members in the process called ""Eastern Enlargement"" or ""Big Bang Enlargement"" in 2004. Looking at these countries by their geographical location, it will be seen that the two are from the Balkans and the eight are from the former Eastern Bloc countries. However, Bosnia and Herzegovina, a Balkan country, has not yet become a candidate country. Bosnia and Herzegovina, which began its relations with the EU in 1992, received assistance in areas such as humanitarian aid and communication. As a result of these developments, progressive relations ensured that in June 2003 Bosnia and Herzegovina was the potential candidate country for the EU. Since it has not fulfilled the criteria for becoming a candidate country for the past 15 years, it is currently a potential candidate country. In this study, Bosnia and Herzegovina’s candidacy / membership process for the EU, which has recently experienced a devastating war and is not fully stable politically, has been assessed economically (Copenhagen and Maastricht criteria). As a result of the assessment, Bosnia and Herzegovina is at an early stage in terms of the Copenhagen economic criterion - in the development of a functioning market economy and in the creation of capacity to cope with competition pressure and market forces within the Union. However, the country has met criteria outside the interest rate (inflation, public debt, budget deficit) from the Maastricht Convergence Criteria.